2019
DOI: 10.26502/jsr.2642-10020033
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Leads to Premature Surgeon Retirement: A Nationwide Survey

Abstract: Background: Retirement of surgeons has important workforce implications given the shortage of surgeons throughout the country. Our study was designed to evaluate factors that influence surgeon retirement decisions. Material and methods:A paper-based survey regarding retirement decisions was mailed nationwide from April to June of 2018 to retired General, Colorectal, Vascular, and Cardiothoracic surgeons that are members of the American College of Surgeons.Results: A total of 2295 of 5282 surveys were completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Before the pandemic, vascular surgeons appeared to be at a high risk for burnout, suicide, low career satisfaction, and quality of life [39] , [40] , [41] . Recognizing the association between surgeon burnout, patient outcomes, and workforce retention [42] , [43] , [44] , the Society for Vascular Surgery (SVS) Wellness Taskforce was created in 2017 and was charged with assessing and addressing vascular surgeon burnout, with the aim of improving member wellness. In 2018, the Wellness Task Force disseminated a survey to the SVS society members to identify the prevalence of burnout, depression, and suicidal ideation among practicing vascular surgeons to guide future policy, advocacy, and member programs to support this workforce crisis.…”
Section: Covid-19 Impact On Vascular Surgeons and Burnoutmentioning
confidence: 99%
“…Before the pandemic, vascular surgeons appeared to be at a high risk for burnout, suicide, low career satisfaction, and quality of life [39] , [40] , [41] . Recognizing the association between surgeon burnout, patient outcomes, and workforce retention [42] , [43] , [44] , the Society for Vascular Surgery (SVS) Wellness Taskforce was created in 2017 and was charged with assessing and addressing vascular surgeon burnout, with the aim of improving member wellness. In 2018, the Wellness Task Force disseminated a survey to the SVS society members to identify the prevalence of burnout, depression, and suicidal ideation among practicing vascular surgeons to guide future policy, advocacy, and member programs to support this workforce crisis.…”
Section: Covid-19 Impact On Vascular Surgeons and Burnoutmentioning
confidence: 99%
“…Previous literature has shown that workrelated pain, discomfort, and musculoskeletal disorders (MSDs) are prevalent among surgeons (Davis et al, 2014;Howarth et al, 2019;Wohlauer et al, 2021). These problems are associated with surgeon burnout and early retirement (Cimbak et al, 2019;Davila et al, 2019;Coleman et al, 2021;Wohlauer et al, 2021) and may discourage medical students from pursuing surgical careers (Sergesketter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Physical pain due to muscular fatigue has been shown to impact cognitive attentional resources (Stephenson et al, 2020) and decision-making (Koppel et al, 2017), potentially affecting surgical outcomes. In addition, 26% of retirees ended their careers owing to physical disabilities from work-related pain (Wohlauer et al, 2021) and high work-related physical pain and discomfort has been found to be highly correlated with burnout (Wohlauer et al 2021;Coleman et al, 2021;Cimbak et al, 2019). Further, musculoskeletal disorder/ergonomic issues were found to be a possible factor that deters medical students from surgical careers (Sergesketter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%